The Effect of Foaming on Mechanical and Morphological Properties of Polypropylene - TAŞDEMİR, MÜNİR (My University, 2022)
The automotive industry is among the priority technology areas of our country, and the reduction of vehicle weight and fuel consumption and thus CO2 emissions without compromising safety criteria are among the priority research areas. For this reason, R&D studies on increasing the use of polymer-based materials in the automotive industry are of great importance. In order to produce \"high strength and weight reduction parts\" in plastic moulding technologies, advanced technologies that focus on cost reduction and efficiency are being implemented rapidly. The chemical foaming process, which provides many advantages such as reducing the consumption of plastic material used, reducing the total moulding cycle time, using less tonnage injection moulding machines, and thus reducing the energy costs, is one of the innovative technologies that have been implemented since a very recent time. In this study, chemical foaming agent were being reinforced at the rate of 1-2-3% in natural fiber-reinforced recycled composite polypropylene raw material. The samples obtained in the injection machine was be moulded in the sizes and shapes in accordance with the standards. Tensile, hardness, impact and three points bending tests would be done. By examining the test results, the mechanical, and morphological properties of natural fiber reinforced polypropylene materials at different chemical agent percentages were examined. With increasing the amount of foaming agent, mechanical properties decreased.
Keywords: Metalurji ve Malzeme Mühendisliği; Malzeme Bilimi ve Mühendisliği; Polimerik Malzemeler; Mühendislik ve Teknoloji; Metallurgical and Materials Engineering; Material science and engineering; Polymeric Materials; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; METALURJİ VE METALURJİ MÜHENDİSLİĞİ; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; METALLURGY & METALLURGICAL ENGINEERING; Polypropylene; composites; chemical foam; plastic injection; mechanical properties.; Polypropylene; Composites; Chemical Foaming; Plastic Injection; Mechanical Properties